Iqbāl's Position on Western Civilization - Shamsud, Professor Dr Salahuddin Bin Mohd (IJRDO - Journal of Social Science and Humanities Research, 2021)
This research deals with Muhammad Iqbāl's position on the Western civilization, communism and capitalism. Iqbāl believes that the social origins offered by Islam can be the best way to unite the humanity, and then deals with his position on the westernization movements in the East means politeness and education of Islamic countries on the Western approach called by ᾽Abu Ṭālib Khān in India and Rifa῾a Al-Ṭaḥṭāwī in Egypt, each of them was pioneers of westernization, carrying the same message. It was then called by Sayyid ᾽Aḥmad Khān, the first pioneer of westernization in the modern history of India's Islamic entity, then by his colleague Sayyid Charāgh ῾Alī, then the character of Sayyid Mumtāz ῾Alī appeared who had been calling for the reformation and women's liberation in his magazine: "Women's Politeness" since 1878, as well as he called for full equality between the men and women in his book: "Women's Rights", and then there were many personalities and multiple schools of thought. Aim of this research is to focus on the character of Muhammad Iqbāl who played a prominent role in the development of Islamic thought in modern India, who was afraid that the call for the westernization in the East could be a ploy to imitate the West, so he criticized Kamal Ataturk in a style of harsh criticism. He addressed the material Western civilization in his poetry, and studied the Western education system and its consequences in modern schools as the education was an essential part of human civilization.